Evercrossed / 4. - Chandler, Elizabeth, 1954- (Kissed by an angel, 2011)
Ivy is looking forward to a relaxing summer in the hopes of erasing the memories of the previous summer, when she lost her best friend Tristan, but when Ivy is involved in a serious car accident and Tristan sends her back from the afterlife, all Ivy can think about is the love she has lost and her missed chance to be reunited with Tristan.